All shades of every color : an overview of early teaching and learning of foreign languages - Mihaljević-Djigunović, Jelena (Array, 2011)
The paper analyzes research published over the last five years. The first part looks into policy documents, types of programs, and surveys to identify 1) reasons why an early start to learning languages is seen as beneficial and under what conditions ; b) possible threats ; c) the aims and expected outcomes that are predicted by various models. The second part discusses studies on learners including what they do in classrooms, how they perform on tasks, how their languages interact, and how they develop in different skills. A separate section reviews individual differences in the affective, cognitive, and strategic domains as well as the role of learners’ socioeconomic status, and their learning difficulties. In the third part, we draw on classroom observation and interview studies to discuss teachers’ roles, proficiency and uses of languages, and beliefs and practices. In the fourth part, we focus on the assessment of young learners ; more specifically, we review what the construct of assessment is, what various assessment frameworks include, what international and national examinations exist, and assessment for learning involves. Finally, in the last section we review implications for further research.